Reliability and Validity of a Chinese Version of Adaptive Cognitive Evaluation Tool in College Students - Yu Z; Wang Y; Li Y; Feng W (Psychology Research and Behavior Management)
Ze Yu,1,2,* Youyang Wang,1,2,* Yiyun Li,3 Wei Feng1,2 1Department of Psychological Medicine, Fudan University Shanghai Cancer Center, Shanghai, 200032, People’s Republic of China; 2Department of Oncology, Shanghai Medical College of Fudan University, Shanghai, 200032, People’s Republic of China; 3Stomatological Hospital and Dental School of Tongji University, Shanghai, 200072, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Feng, Department of Psychological Medicine, Fudan University Shanghai Cancer Center, Shanghai, 200032, People’s Republic of China, Email ffww06@163.comBackground: Cognition is central to acquiring knowledge and learning new experiences, critical for social behavior and quality of life. Despite its importance, traditional cognitive assessment tools face limitations, including high labor costs and human error, underscoring an urgent need for cost-effective, precise tools to assess cognitive functions.Objective: This study aims to address this gap by evaluating the reliability and validity of the Chinese version of the Adaptive Cognitive Evaluation (ACE) tool among college students, thereby contributing to the advancement of cognitive research and disease management strategies in China.Methods: We collected data from 150 participants (72 males, 78 females) with an average age of 20.97 ± 3.36 years. A baseline assessment was conducted using the ACE Chinese version, Digit Span Memory Test (DSMT), and Line-trailing Test-A & B (LTT-A&B). After one week, the ACE tests were administered again to assess test–retest reliability.Results: The results indicated no significant correlations between age, sex, and the outcomes of the sub-tests. However, a significant association was found between educational level and the results of the sub-tests. The Cronbach’s α for each sub-test exceeded 0.8, indicating high reliability. Both the I-CVI and S-CVI indexes were 1.00, demonstrating strong content validity. When DSMT, LTT-A, and LTT-B were used as criteria, most sub-tests showed satisfactory criterion validity. The factor-loading coefficient for each dimension of cognitive control was greater than 0.4, and the cumulative variance explanation rate was 64.84%.Conclusion: The Chinese version of the ACE tool demonstrated satisfactory reliability and validity, making it an efficient tool for cognitive function assessment among college students.Keywords: cognitive control, adaptive cognitive evaluation, reliability, validity